Falsos cognatos francês-português entre termos de estatutos sociais - Teles, Letícia Bonora [UNESP] (2010)
In this article we address the search for equivalents in the elaboration of a model dictionary for sworn translators of terms used in bylaws, in the Portuguese-French translation direction. We present, specifically, some cases in which the morphological similarity between the two languages can lead to errors, for example false cognates.